Long-run determinants of the real exchange rate: Brazil - 1947/95 - Antonio Fiorencio; Ajax Reynaldo Bello Moreira (Institute for Applied Economic Research (ipea), 2015)
This paper presents a model for the long-run determinants of the Brazilian real exchange rate for the period 1947/95. This is a simple representative agent model that links the exchange rate, external debt and net exports. It is assumed that: a) the country pays an interest rate on its debt which is an increasing function of the debt/GDP ratio; b) the real exchange rate is a control variable. The transitional dynamics of the model following different shocks is analysed. The model suggests that the relevant variables are the real exchange rate, external debt and net exports. A VEC model using these variables shows that the Brazilian data support the existence of one cointegrating relation among the three variables, which we interpret as the empirical counterpart of the long-run conditions of the theoretical model. Finally, we impose restrictions to identify shocks that could be interpreted as the non-observable exogenous variables of the theoretical model. The dynamics of the empirical model is estimated.
Keywords: 330